The Genesis of Violence and Self-Destruction in George Lamming’s Water With Berries - Harbi Mahdi Al-Azawi, Basma (Al-Adab Journal, 2018)
This paper examines George Lamming’s Water with Berries, a postcolonial text, to reveal the counter literary strategy used by the writer to redefine the colonized against the Western cultural hegemony and the attempts done by the colonial writers to misrepresent and stereotype the colonized people. The paper discusses how the counter text with its alternative interpretation challenges the constitution upon which the canonical work has been based. Re-writing and writing back represent the textual resistance to the misrepresentations and ideas expressed by the center.Lamming explores the colonial experience and its effects on the social, moral, cultural values of previously colonized people. By re-writing Shakespeare’s The Tempest, Lamming provides an alternative reading that might appropriate or undermine the original text. Thus, writing from a post-colonial perspective creates a new perception of colonialism and its effects.